Inovasi Pemuda Dalam Mengembangkan Ekonomi Kreatif Melalui Produksi Sirup Markisa Di Desa Pattongko Kecamatan Sinjai Tengah - Ulfayanti; Anisa, Andi; Nurvaika, Nurvaika; Aminah, Sitti (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2022)
Youth innovation is an important thing in the implementation of a village development program, one of which is in the creative economy development program. This study aims to determine Youth Innovation in Developing Creative Economy through Passion Fruit Syrup Production in Pattongko Village, Central Sinjai District. The research, which was conducted in Pattongko Village, Central Sinjai District, Sinjai Regency, used qualitative methods in collecting data. The data collection techniques used were observation, interviews, and documentation. The data analysis technique used the theory of Miles and Huberman which includes data collection, data reduction, and data presentation. Through this research, researchers found the fact that in Pattongko Village there are many things that can be done by youth in developing the village. One of them was pioneered by Asmar Anugrah, an inspiring young man who became an entrepreneur from passion fruit plantations. Therefore, the existing passion fruit is processed into syrup and labeled "Anugrah Markisa". This business was born from the desire to add value to passion fruit which was originally considered to have no market. In addition, this effort is expected to motivate farmers so that the fruit can be a source of income by processing it into syrup. Another benefit that can be provided is that it can help the government overcome the poverty level through the creation of business opportunities. Based on the findings above, it can be said that Anugrah Markisa, an innovation pioneered by youth provides a real contribution to the development of the creative economy by showing that youth provide an innovation or new idea in the production of passion fruit syrup and also provides job opportunities for farmers by buying their crops to be processed into syrup.